Penerapan Standar-Standar Perlindungan Utama dan Refleksinya dalam Foreign Direct Investment (FDI) - Manik, Rosari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The flow of Foreign Direct Investment (FDI) plays a vital role in driving global economic growth. This journal provides a comprehensive analysis of the five principal standards of protection enshrined in Bilateral Investment Treaties (BITs) and customary international law, namely Fair and Equitable Treatment (FET), Full Protection and Security (FPS), the Non-Discrimination Principle (Most-Favoured-Nation and National Treatment), and Protection against Nationalization and Expropriation. Through an examination of arbitral interpretations and a reflection on Indonesia’s domestic regulations, this study finds that standards such as FET have evolved beyond the conventional International Minimum Standard (IMS), and that protection against expropriation is no longer limited to direct takings but also encompasses indirect regulatory measures. For Indonesia, the implementation of these standards requires a careful balance between attracting foreign capital and preserving domestic policy space, particularly in addressing the challenges of regulatory chill and unequal treatment between foreign and domestic enterprises.